Ziziphi spinosae lily powder suspension in the treatment of depression-like behaviors in rats - Yifang Wang; Mei Huang; Xinyi Lu; Runze Wei; Jinyong Xu (BMC, 2017)
Abstract Background Depression is a chronic, recurring and potentially life-threatening illness. Current treatments for depression are characterized by a low success rate and associated with a wide variety of side effects. The aim of the present study was to evaluate the behavioral anti-depressant effect of a novel herbal compounds named ziziphi spinosae lily powder suspension, as well as to investigate its potential mechanisms. Methods Except for body weight, depressive-like behaviors were also evaluated using forced swimming test, sucrose consumption test and open field test. In order to investigate the underlying potential mechanisms, serum 5-HT and brain 5-HIAA were measured using ultrahigh-performance liquid chromatography and high-performance liquid chromatography, respectively. Results Results showed that the herbal compounds ziziphi spinosae lily suspension could alleviate depressive symptoms in rat model of chronic depression. Biochemical analysis revealed that the herbal compounds elevated serum 5-HT and brain 5-HIAA. Conclusion Ziziphi spinosae lily powder suspension could alleviate depressive behaviors in depression model animals. The underlying mechanisms may be related to the increase of serum 5-HT in peripheral blood and 5-HIAA in brain. The study provides important mechanistic insights into the protective effect of the herbal compounds against chronic depressive disorder and suggests that the herbal compounds may be a potential pharmacological agent for treatment of major depressive disorder.